1995
DOI: 10.3177/jnsv.41.227
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Protein on the Induction of DNA Synthesis and Expression of Growth-Related Genes in Liver and Kidney of Growing Rats.

Abstract: SummaryTo investigate molecular mechanisms of growth control by protein nutrition, we examined whether nutritive quality of protein affects the induction of DNA synthesis in liver and kidney of growing rats in relation to expression of growth-related genes such as c-myc, c-fos, c-Ha-ras, and ornithine decarboxylase (ODC). Rats were adapted to 2-h meal feeding schedule at first with laboratory chow for 10 days and then with a protein-free diet for 3 days prior to experiments. When protein free diet was fed to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

1995
1995
1999
1999

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 35 publications
(21 reference statements)
1
6
0
Order By: Relevance
“…Therefore, it seems likely that the level of c-myc mRNA in cultured hepatocytes is mainly regulated by amino acids. On the other hand, the level of ODC and c-Ha-ras mRNAs were not influenced by the medium change although they were increased in the growing rat liver by feeding of protein-free diet (7), suggesting that factors other than amino acids were involved in the regulation of the expression of these two mRNAs. In fact, we have reported that glucagon increases the level of ODC mRNA in cultured hepatocytes incubated either in the presence or absence of amino acids (12).…”
Section: And Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…Therefore, it seems likely that the level of c-myc mRNA in cultured hepatocytes is mainly regulated by amino acids. On the other hand, the level of ODC and c-Ha-ras mRNAs were not influenced by the medium change although they were increased in the growing rat liver by feeding of protein-free diet (7), suggesting that factors other than amino acids were involved in the regulation of the expression of these two mRNAs. In fact, we have reported that glucagon increases the level of ODC mRNA in cultured hepatocytes incubated either in the presence or absence of amino acids (12).…”
Section: And Discussionmentioning
confidence: 87%
“…We recently reported that hepatic levels of several growth-related gene trans cripts, such as c-myc, ornithine decarboxylase (ODC) and c-Ha-ras mRNAs were elevated when growing rats were fed protein-free diets (6,7). To determine whether the expression of these growth-related genes were affected directly by changes in the nutritional environment, we examined the levels of these mRNAs in cultured hepatocytes in the presence and absence of amino acids.…”
Section: And Discussionmentioning
confidence: 99%
See 3 more Smart Citations